Tuning the photonic properties of chiral nematic mesoporous organosilica with hydrogen-bonded liquid-crystalline assemblies1. Issue 7 (21st February 2015) - Giese, Michael; Krappitz, Tim; Dong, Ronald Y.; Michal, Carl A.; Hamad, Wadood Y.; Patrick, Brian O.; MacLachlan, Mark J.
<x xml:space="preserve">Abstract</x> The thermochromic behaviour of chiral nematic mesoporous organosilica hybrids infiltrated with hydrogen-bonded liquid crystals was investigated by polarized optical microscopy, UV-vis and CD-spectroscopy.